Effectiveness of switching between TNF inhibitors in ankylosing spondylitis: data from the NOR-DMARD register. Issue 1 (9th November 2010) - Lie, E; van der Heijde, D; Uhlig, T; Mikkelsen, K; Rødevand, E; Koldingsnes, W; Kaufmann, C; Kvien, T K
Abstract : Objective: To assess the effectiveness of switching to a second tumour necrosis factor inhibitor (TNFi) in patients with ankylosing spondylitis (AS). Methods: Data were extracted from an ongoing longitudinal observational multicentre study in Norway. This study included anti-TNF naïve patients with AS starting treatment with a TNFi as well as treatment with a second TNFi in these same patients. Effectiveness data and 2-year drug survival were compared between switchers and non-switchers and within switchers (first and second TNFi). Results: 514 anti-TNF naïve patients with AS were included; 77 patients switched to a second TNFi while 437 patients did not switch. The percentages of non-switchers using etanercept, infliximab or adalimumab were 53%, 32% and 15%, and the percentages of first and second TNFi in the switchers were 42%, 53% and 5% and 40%, 23% and 36%, respectively. The reason for switching was insufficient response (IR) in 30, adverse events (AEs) in 44 and not reported in 3 patients. Baseline disease activity was similar between the groups. Three-month BASDAI 50 and ASAS 40 responses were achieved by 49% and 38% of non-switchers, by 25% and 30% of switchers after the first TNFi and by 28% and 31% after the second TNFi. The 3-month disease activity level was higher for switchers on the second TNFi than for non-switchers. Drug withdrawal rate was higher during the second TNFi among switchers than for non-switchers (p=0.001). No difference was found in the effectiveness of the second TNFi between switchers due to IR and AE. Conclusion: This study confirms that switching to a second TNFi can be effective in AS and can be as useful as in rheumatoid arthritis, although overall effectiveness seems to be somewhat lower than in non-switchers.